2019
DOI: 10.1136/bmjopen-2019-030084
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors affecting catch-up growth after infant congenital heart disease surgery: rationale and design of a multicentre prospective cohort study in China

Abstract: IntroductionSuccessful surgical treatment of congenital heart disease improves neonates’ long-term survival and leads to catch-up growth, which however does not occur in part of the patient population for largely undetermined reasons.Methods and analysisA multicentre, prospective cohort study is being conducted in four paediatric medical institutions in China to collect detailed nutritional, anthropometric and clinical data at perioperative phases and during a 1-year period of follow-up after surgery. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
4
0
4
Order By: Relevance
“…Furthermore, the number of CHD patients aged older than five years in the present study was small and did not have adequate power to make a strong conclusion. Previously, several studies found that CHD patients could catch-up growth significantly after corrective cardiac surgery in both cyanotic and acyanotic CHD (Carmona et al, 2012;Cheung et al, 2003;Li et al, 2019). Martins et al, demonstrated that early VSD closure resulted in significant acceleration of post-operative growth within 3-6 months in both term and preterm infants (Correia Martins et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the number of CHD patients aged older than five years in the present study was small and did not have adequate power to make a strong conclusion. Previously, several studies found that CHD patients could catch-up growth significantly after corrective cardiac surgery in both cyanotic and acyanotic CHD (Carmona et al, 2012;Cheung et al, 2003;Li et al, 2019). Martins et al, demonstrated that early VSD closure resulted in significant acceleration of post-operative growth within 3-6 months in both term and preterm infants (Correia Martins et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is a prospective cohort study carried out at Guangzhou Women and Children's Medical Center in China (registration number: NCT03626480), and the details of this longitudinal cohort study have been previously published 15 . In summary, we included patients admitted to a single academic center (Guangzhou Women and Children's Medical Center) with a diagnosis of CHD according to the International Classification for Diseases, 10th version 16 .…”
Section: Methodsmentioning
confidence: 99%
“…The GHRIC study is primarily an epidemiological investigation without any predefined statistical hypothesis to test, making a priori sample size calculation unnecessary. 21 In designing this study, we wished to ensure that we obtained the correct answers in the most efficient way, so that the work that we do will be worthwhile. Therefore, we will enrol enough HRIs to give our results adequate power, but not too many that we waste time gathering more data than we need.…”
Section: Methodsmentioning
confidence: 99%